PENGARUH ABU KULIT DURIAN DAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS PADA TANAH GAMBUT - Saifuddin saifuddin; Henny Sulistyowati; Evi Gusmayanti (Jurnal Sains Pertanian Equator, 2017)
The research is aimed to determine the effect of ash and cow manure on growth and yield of sweet corn cultivated  on peat soil. Ash applied in this study was prepared from durian shell. The research was held at Sungai Kakap, one of durian producer area in Kubu Raya District, West Kalimantan. The experiment is arranged  according to factorial randomize block design with two factors, i.e., dosage of ash (Factor A) and dosage of cow manure (Factor B). Factor A consists of three levels is, a1 (30 ton/ha equivalent to 8,07 kg/plot), a2 (41 ton/ha equivalent to 11,21 kg/plot), a3 (47 ton/ha equivalent to 14,35 kg/plot) and factor B also consists of b1 (10 kg/ha equivalent to 5kg/plot), b2 (20 kg/ha equivalent to 10 kg/plot), b3 (30 kg/ha equivalent to 15 kg/plot). Every treatments is replicated 4 times, and each of this experimental unit has three sample crops. The results showed that interaction of factor A and factor B has not significantly affected growth and yield of sweet corn. The main effect of Factor B has been identified statistically significant. Among the levels of Factor B, application of 10 kg cow manure per plot (equivalent to 20 ton/ha) is considered as the best dosage in this study.